Intolerância religiosa no Recife: cartografia das denúncias e enfrentamentos entre 2014 e 2019. - Leal, Rayane Marinho (2022)
This study develops an analysis of religious intolerance in the city of Recife, between 2014 and 2019. It’s objective is to test the bases for a database on intolerance and religious violence in Recife, with a view to filling a lack of specific information found in reports on human rights violations, especially with regard to Guiding Axis III, Directive 10, of the National Human Rights Program (PNDH-3). In the elaboration of this dissertation, bibliographic reviews were carried out in books and articles on religious violence and respect for spiritual diversity, as well as on laws and legal norms on the secularity of the State. Surveys were also carried out in archives and in the press, in addition to interviews with lawyers and legal agents, representatives of the legislature, religious leaders and civil personalities who contribute to the fight against religious violence, aiming to expose different narratives on the subject. A thematic cartography was used as the main methodology, mapping the main religions in the city and the exemplary cases of intolerance and religious violence. As a result, the characteristics of religious intolerance in the Recife metropolis were observed and the paths already taken to overcome the presented problem were highlighted. In the end, it is clear that social relations are constantly changing on the map of the city and can be transformed and humanized from a positive consideration of cultural plurality and made possible by the practice of dialogue. There is a need to therapeuticize religious discourses, which will only be able to advance towards social coexistence and interreligious dialogue by overcoming associations of spiritual diversity with an “original sin” and by linking them to a blessing of origins.